2018
DOI: 10.1177/1724600817748539
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the potential value of 5-fluorouracil metabolic enzymes in predicting prognosis and treatment response of colorectal cancer patients

Abstract: The above findings suggest that coexpression of 5-FU metabolic enzymes possess significant prognostic value and could be useful biomarkers in colorectal cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Even so, its direct correlation in 5-FU treatment outcome was previously a subject of debate as certain studies linking elevated expression with worse patient prognosis [ 242 , 243 , 244 ]. Recent studies later conclusively determined that TYMP overexpression may only benefit early-stage patients in prolonging time to disease progression, relapse-free survival, and OS [ 229 , 230 , 231 , 232 , 233 , 245 ]. This is supported by experimental studies in which enhanced 5-FU cytotoxicity is observed in conditions where TYMP is upregulated in colon cancer cells and xenograft mice [ 234 , 246 ].…”
Section: Mechanism Of Resistance By Key 5-fluorouracil Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, its direct correlation in 5-FU treatment outcome was previously a subject of debate as certain studies linking elevated expression with worse patient prognosis [ 242 , 243 , 244 ]. Recent studies later conclusively determined that TYMP overexpression may only benefit early-stage patients in prolonging time to disease progression, relapse-free survival, and OS [ 229 , 230 , 231 , 232 , 233 , 245 ]. This is supported by experimental studies in which enhanced 5-FU cytotoxicity is observed in conditions where TYMP is upregulated in colon cancer cells and xenograft mice [ 234 , 246 ].…”
Section: Mechanism Of Resistance By Key 5-fluorouracil Enzymesmentioning
confidence: 99%
“…•Meta-analysis: poor patients' prognosis when TYMP is suppressed[229].•Increase disease recurrence in patients with TYMP underexpression[230].•Low TYMP expression is associated with reduced patients' relapse-free survival (RFS)[231].•Low TYMP is associated with poor patient outcome[232].…”
mentioning
confidence: 99%
“…A few Indian studies have explored the association of DPYD variants with 5‐FU/capecitabine‐mediated toxicity 11–16,24 . Low DPYD expression was linked to unfavourable overall survival in colorectal cancer patients 24 .…”
Section: Discussionmentioning
confidence: 99%
“…A few Indian studies have explored the association of DPYD variants with 5‐FU/capecitabine‐mediated toxicity 11–16,24 . Low DPYD expression was linked to unfavourable overall survival in colorectal cancer patients 24 . DPYD*9A (rs1801265) variant was found to increase the risk for the hand‐foot syndrome, diarrhea and thrombocytopenia following treatment with capecitabine and oxaliplatin in colorectal cancer 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been many therapeutic drugs for colorectal cancer. Fluorouracil drugs represented by 5-Fu are the cornerstone of colorectal cancer chemotherapy (Gajjar et al, 2018). During the treatment of recurrent tumors, stubborn tumor cells will produce chemotherapy.…”
Section: Introductionmentioning
confidence: 99%